2013
DOI: 10.1371/journal.pone.0066970
|View full text |Cite
|
Sign up to set email alerts
|

High Cholesterol Diet Induces IL-1β Expression in Adult but Not Larval Zebrafish

Abstract: Recently, it has been demonstrated that high cholesterol diet induced hypercholesterolemia and vascular lipid oxidation and accumulation in zebrafish larvae, suggesting that zebrafish is a new promising atherosclerosis model in addition to mouse models. However, up to date, there was no report regarding inflammatory cytokine expression during the lipid accumulation in zebrafish larva and adult fish. In this study, we first demonstrated the expression levels of IL-1β and TNF-α in high cholesterol diet (HCD)-fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Third, to facilitate the detection of cardiomyopathy phenotypes, we imposed two stresses. Previous studies showed that feeding adult fish a high cholesterol diet induces hypercholesterolemia and atherosclerotic changes [ 44 , 45 ]. Additionally, ethanol exposure interrupts cardiac morphogenesis, causing heart defects in zebrafish embryos [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, to facilitate the detection of cardiomyopathy phenotypes, we imposed two stresses. Previous studies showed that feeding adult fish a high cholesterol diet induces hypercholesterolemia and atherosclerotic changes [ 44 , 45 ]. Additionally, ethanol exposure interrupts cardiac morphogenesis, causing heart defects in zebrafish embryos [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 4% cholesterol diet was made as previously descripted [ 44 , 45 ]. Briefly, 4 g cholesterol (Sigma, St. Louis, MO, USA) was dissolved in 200 mL ether before being mixed with 100 g of artificial artemia.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish ␤-actin was used as standard to control for the starting quantity of RNA. The sequences of PCR primers were: 5 -GAGGAGCACCCCGTCCTGCTCAC-3 and 5 -GATGGCTGGACCAGGGCCTCTGG-3 for ␤-actin, 5 -TGGCGA ACGTCATCCAAG-3 and 5 -GGAGCACTGGGCGACGCATA-3 for IL-1␤, 5 -TCAACTTCTCCAGCGTGATG-3 and 5 -TCTTTCCCTCTTTTCCTCCTG-3 for IL-6, and 5 -GCTTATGAGCCATGCAGTGA-3 and 5 -TGCCCAGTCTGTCTCCTTCT-3 for TNF-␣ (Yoon et al, 2013). PCR was performed with an initial denaturation of 5 min at 95 • C, then 35 cycles were run for 30 s of denaturation at 95 • C, 30 sec of annealing at 55 • C, and 30 s of extension at 72 • C. The cycle threshold (CT) value was calculated to indirectly assess relative changes in expression levels based on the 2 − CT method (Livak and Schmittgen, 2001).…”
Section: Gene Expression Assaymentioning
confidence: 99%
“…tumor necrosis factor α (TNF-α) and interleukin-1β (IL-1β) from adipose tissues) (Coppack, 2001[ 11 ]; Zoccali et al, 2003[ 45 ]). In parallel, it is also reported that hypercholesterolemia and high cholesterol diet could increase the production of TNF-α and IL-1β, resulting in the amplification of inflammatory process (Kotnik et al, 2013[ 21 ]; Sell and Eckel, 2007[ 35 ]; Yoon et al, 2013[ 40 ]).…”
Section: Discussionmentioning
confidence: 99%